2015
DOI: 10.1002/bio.2998
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the interaction of cefpirome sulfate with lysozyme by fluorescence quenching spectroscopy and synchronous fluorescence spectroscopy

Abstract: The reaction mechanism of cefpirome sulfate with lysozyme at different temperatures (298, 310 and 318 K) was investigated using fluorescence quenching and synchronous fluorescence spectroscopy under simulated physiological conditions. The results clearly demonstrated that cefpirome sulfate caused strong quenching of the fluorescence of lysozyme by a static quenching mechanism. The binding constants obtained using the above methods were of the same order of magnitude and very similar. Static electric forces pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 34 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…However, the interaction of doxofylline with Lys altered the emission maxima peak with a redshift for Δλ = 15 nm, showing an increase in polarity around tyrosine and thereby lowering the hydrophobicity of it [27]. It is obvious from the data that interaction of doxofylline with Lys produced apparent changes in conformation of Lys [28]. Using the modified Stern-Volmer plot, K b was obtained as 2.29 × 10 4 M −1 .…”
Section: Synchronous Fluorescence Examinationmentioning
confidence: 98%
“…However, the interaction of doxofylline with Lys altered the emission maxima peak with a redshift for Δλ = 15 nm, showing an increase in polarity around tyrosine and thereby lowering the hydrophobicity of it [27]. It is obvious from the data that interaction of doxofylline with Lys produced apparent changes in conformation of Lys [28]. Using the modified Stern-Volmer plot, K b was obtained as 2.29 × 10 4 M −1 .…”
Section: Synchronous Fluorescence Examinationmentioning
confidence: 98%
“…It is classified into positive cooperativity, negative cooperativity and non-cooperativity according to the promotion or inhibition of the affinity for other ligand molecules. Usually, Hill's coefficient was used to determine the cooperativity of the drug and protein [35] , which can be calculated graphically on the basis of the following equation: Table 5. The values of n H were < 1 in the systems at different temperatures, which indicated that there is negative cooperation in the interaction of Cefpirome with Trypsin.…”
Section: Hill's Coefficient Of the Trypsin-cefpirome Systemmentioning
confidence: 99%